Emergence and Genomic Characterization of Neisseria gonorrhoeae Isolates with High Levels of Ceftriaxone and Azithromycin Resistance in Guangdong, China, from 2016 to 2019 - Lin, Xiaomian; Chen, Wentao; Yu, Yuqi; Lan, Yinyuan; Xie, Qinghui; Liao, Yiwen; Wu, Xingzhong; Tang, Sanmei; Qin, Xiaolin; Zheng, Heping (Microbiology spectrum, 2022)
Here, we report five sporadic dual-resistant isolates, including FC428-related ceftriaxone-resistant clones with MICs of ≥0.5 mg/L and high-level azithromycin resistance with MICs of ≥1,024 mg/L. This study highlights that dual-resistant clones with the same evolutionary origin as FC428, A2735, and F89 have circulated in Guangdong, China, which suggests that the capacity for antibiotic resistance testing and genome analysis should be strengthened in daily epidemiological surveillance. Currently, antibiotic resistance (especially ceftriaxone and azithromycin dual resistance) in Neisseria gonorrhoeae is the main obstacle affecting the efficacy of treatment. As analysis of drug sensitivity, molecular features, and dissemination of dual-resistant strains is important for gonococcal prevention and control, MIC, genotyping, and genome analysis were conducted to reveal the molecular characteristics and phylogeny of N. gonorrhoeae isolates. During 2016 to 2019, 5 out of 4,113 strains were defined as dual-resistant clones, with ceftriaxone MICs of 0.25 to ≥1 mg/L and azithromycin MICs of 2 to ≥2,048 mg/L. In particular, two strains with a ceftriaxone MIC above 0.5 mg/L were characterized as penA -60.001 FC428-related clones, and two isolates with a high-level azithromycin MIC above 1,024 mg/L featuring a 23S rRNA mutation were identified. Furthermore, phylogenetic analysis confirmed that the dual-resistant strains were closer to the evolutionary origin of F89 in France, global FC428-related clones, and high-level dual-resistant clones in Australia and the United Kingdom. Dual-resistant strains, including FC428-related clones and high-level azithromycin-resistant clones, have circulated in Guangdong, China. The ability of laboratories to perform real-time drug susceptibility and genetic analyses should be strengthened to monitor the spread of threatening strains. IMPORTANCE Here, we report five sporadic dual-resistant isolates, including FC428-related ceftriaxone-resistant clones with MICs of ≥0.5 mg/L and high-level azithromycin resistance with MICs of ≥1,024 mg/L. This study highlights that dual-resistant clones with the same evolutionary origin as FC428, A2735, and F89 have circulated in Guangdong, China, which suggests that the capacity for antibiotic resistance testing and genome analysis should be strengthened in daily epidemiological surveillance.